تعليم أساليب الترجمة لمتعلمي العربية بالمرحلة الجامعية بماليزيا /bcإعداد، أشواق محمد صالح كنالي - Ashwaq Muhammad Salleh Kenali (Kulliyyah of Islamic Revealed Knowledge and Human Science, International Islamic University Malaysia, 2009)
This study discusses teaching translation methods to undergraduate students in Malaysia, and its impact on their language performance. Using descriptive and experimental methodologies, this study establishes a connection between translation and teaching Arabic as a second language, and notes that learners commit errors in using the second language due to mother tongue interference and the impact of literal translation. This study relates learners' shortcomings translating and transferring ideas into the second language to the ignorance of the right methods of translation. The discussion includes the theorical and practical aspects of translation methods, as well as translation problems faced by learners in selecting words, structures, styles and cultural norms. The discussion also includes translation strategies to improve the students' language competence. Practical analysis was conducted by the researcher on a group of students from the Universiti Sains Islam Malaysia (USIM), focusing on cultural and linguistic errors. It is argued that learning translation methods help in developing students' language competence, acquiring second language styles and understanding the socio-culture. The study concludes that language students at undergraduate level simplify need to learn translation methods in order to develop their language competence and performance, and to overcome difficulties resulting from the differences between languages and cultures.